Therapeutic effect of Dongbai-Tonglin-Fang, a Chinese herbal formula, on urinary tract infection in rat model. (15th September 2019) - Li, Xiao-Qin; Zhu, Jian-Yong; Pan, Rong-Rong; Shen, Yu-Li; Rahman, Khalid; Zhang, Chun-Yan; Zhang, Li-Jun; Luan, Xin; Zhang, Hong
Abstract: Ethnopharmacological relevance: Traditional Chinese Medicine (TCM) has many obvious advantages in the treatment of chronic conditions such as urinary tract infection (UTI). Dongbai-Tonglin-Fang (DBTL), a Chinese herbal formula, has been used for the treatment of UTI for more than 40 years with proven efficacy. However, its mechanism of action is still unknown. Aim of the study: The purpose of this study is to evaluate the therapeutic efficacy of DBTL and its mechanism of action in a rat UTI model. Materials and methods: E. coli solution induced UTI rat model was used to evaluate the therapeutic effect of DBTL on UTI. Biochemical indicators related to UTI were measured. The kidney tissue was stained with hematoxylin-eosin (HE) to observe pathological changes whilst the ear swelling, feet swelling, hot plate and body torsion tests were used to estimate the anti-inflammatory and analgesic effects of DBTL. Results: After treatment with different doses of DBTL (1, 2, 4 g/kg), a decrease in weight of the kidney in the UTI rat model was observed. The contents of white blood cell, nitrite, urinary albumin, ketone body, bilirubin and occult blood in the urine were also reduced whilst an increase in the pH of urine was observed. HE staining showed that the pathological changes in the kidney tissue were alleviated. At the same time, ear swelling assay showed that the weight and the degree of swelling of the ear of the mice in DBTL groups were decreased remarkably. DBTL also reduced the degree of feet swelling of the rats caused by the adjuvant. Furthermore, with the DBTL treatment, the latency period of foot licking induced by thermal stimulation was increased while the number of twists was lessened. Conclusion: These results show that DBTL has an excellent therapeutic effect on UTI rats accompanying with anti-inflammation and analgesia. The data presented here lays the foundations for further investigations in the treatment of UTI. Graphical abstract: Image 1